Interconversions of cardiac muscle glycogen synthetase (Revista Española de Fisiología, 1971)
Heart muscle glycogen synthetase can be analyzed as both I and D forms, and the enzyme systems that interconvert them are also active. The percentage of I form that can be analyzed does not always keep an inverse relationship to the amount of glycogen present in muscle in keeping with the findings of others under different experimental conditions.To explain this (apparently abnormal behavior) as well as other findings we pos tulated the possibility of the existence of inactive forms of muscle glycogen synthetase which in frog skeletal muscle have been recently demonstrated for the D form.In this report we present data which demonstrate that the D enzyme form of heart muscle glycogen synthetase can be inactivated by a reaction driven by the addition of ATP and Mg. This inactivation is dependent both on time and the concentration of ATP and is sensitive to the presence of 3Z,5'-AMP, all these conditions indicating a kinase reaction. The inactivating reaction can be arrested and reversed by the addition of strong concentrations of EDTA to trap the necessary Mg'+.In a similar manner I activity can also be inactivated by reactions of the same type, and also the D to I form transformation can be prevented by the addition of ATP-Mg. I activity also reappears after arrested the inactivating reaction by the addition of 20 mM EDTA.All these experimental data lead us to postulate the existence of complete inactive forms of glycogen synthetase from heart muscle which can play a role in the regulation of glycogen metabolism in this organ and can explain some of the observations des cribed by various authors.